Analisis Mutasi Kepala Sekolah Menengah Pertama di Kecamatan Siantan Kabupaten Kepulauan Anambas - Dahrani Dahrani; Afriza Afriza; Agustiar Agustiar; Asrulla Asrulla (Journal of Innovative and Creativity, 2025)
The school principal mutation at SMPN 5 Bukit Tambun and SMPN 2 Siantan has had a significant impact on strategic planning, human resource management (HRM), and teacher performance in both schools. This leadership change triggered positive transformations in the formulation of the vision, mission, and work programs, which are more aligned with current needs, especially in utilizing technology for learning and improving work discipline. At SMPN 5 Bukit Tambun, the principal mutation resulted in an updated vision and mission with a focus on technology-based learning, while at SMPN 2 Siantan, the emphasis was more on strengthening the work discipline culture. Moreover, the mutation improved coordination between the school principal, teaching staff, and administration, leading to better resource management and increased teacher motivation. In terms of HRM, the principal mutation introduced a more structured performance monitoring system, which resulted in higher staff and teacher productivity. Teachers felt more valued and motivated to improve their teaching quality due to technical guidance and opportunities for training. Ultimately, this leadership change also led to an improvement in work discipline among teachers, reflected in punctuality and teaching quality. Overall, the principal mutation in these two schools demonstrates that leadership change can serve as a catalyst for managerial renewal and performance improvement at the secondary education level.